2020
DOI: 10.1007/s12325-020-01394-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns and Outcomes in Patients Receiving Second-Line Therapy for Advanced/Metastatic Esophageal Squamous Cell Carcinoma

Abstract: Introduction: Currently available second-line (2L) therapies for advanced/metastatic esophageal squamous cell carcinoma (adv/met ESCC) include the taxanes paclitaxel and docetaxel. In clinical trials, such therapies have provided only modest improvements in survival. Few studies have assessed outcomes in routine clinical practice in the USA. We compared realworld clinical outcomes in the US for patients receiving taxane or non-taxane 2L therapy for adv/met ESCC. Methods: The Flatiron Health database was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
2
13
0
2
Order By: Relevance
“… 8 , 9 Although NCCN Guidelines provide recommended options for second-line therapy in advanced or metastatic ESCC, much of the evidence base focused on esophageal adenocarcinoma and did not specifically consider ESCC. 10 Therefore, the optimal second-line therapeutic strategy for ESCC remained controversial. To address this issue, the present study aimed to evaluate a promising new second-line therapy option for advanced ESCC patients.…”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%
“… 8 , 9 Although NCCN Guidelines provide recommended options for second-line therapy in advanced or metastatic ESCC, much of the evidence base focused on esophageal adenocarcinoma and did not specifically consider ESCC. 10 Therefore, the optimal second-line therapeutic strategy for ESCC remained controversial. To address this issue, the present study aimed to evaluate a promising new second-line therapy option for advanced ESCC patients.…”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%
“…In ATTRACTION‐3, survival time of patients in the control arm (all receiving taxane monotherapy) was higher at 8.4 months 8 . In a real‐world study of patients with ESCC, the survival of patients receiving second‐line taxane monotherapy (7.3 months) was longer compared with patients receiving other second‐line regimens (5.1 months) 28 . In our study, 22% of patients received second‐line taxane monotherapy and this could explain the shorter survival time compared with ATTRACTION‐3.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in that study the majority of patients was treated with a combination chemotherapy of carboplatin plus paclitaxel, whereas in our study taxanes were administered as a singleagent regimen. 37 We finally aimed to identify predictive markers for second line therapy benefit. In an exploratory propensity score adjusted subgroup analysis we found that the favorable association between longer OS and second-line therapy was consistent across several relevant clinical subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in that study the majority of patients was treated with a combination chemotherapy of carboplatin plus paclitaxel, whereas in our study taxanes were administered as a single-agent regimen. 37 …”
Section: Discussionmentioning
confidence: 99%